Image-Based Neonatal Hyperbilirubinemia Screening after Hospital Discharge - Xiaoyue DONG; Xiaofan SUN; Zhangbin YU; Shuping HAN (Tehran University of Medical Sciences, 2020)
Background: Newborn infants who are risk for severe hyperbilirubinemia and cared at home should be monitored for progression of jaundice. We aimed to verify if a smart phone application (BiliScan Inc), which uses automated imaging for bilirubin (AIB), can be used to estimate total serum bilirubin (TSB) levels at home. Methods: A convenience sample of 1038 "healthy" infants in China were prospectively enrolled to a single-center study in 2016. Correlations between AIB and TcB measurements were correlated to TB measurements. Bias and imprecision of AIB measurements were determined using Bland-Altman analysis. The diagnostic value of AIB was compared by the area-under-curve (AUC) values of receiver operator characteristic (ROC) curves. Results: The best correlation and AUC for AIB were at the sternum, both with values of 0.76. We truncated performances to 369 TB values >5 and <15 mg/dL, and sternal AIB showed the best correlation to TB (r =0.5, P<0.0001). The AUC for this range was 0.54. However, from a subset of 200 AIB values >13.5 mg/dL (n=369 babies), the sensitivity and negative predictive value (NPV) were 100% with a specificity of 50%. Furthermore, Bland-Altman analyses showed a bias and imprecision of AIB and TcB when TB was >13.5 and <15 mg/dL. Conclusion: The use of AIB may be a potentially useful screening device for neonatal jaundice. Its performance requires additional improvements for accurate measurements across wider ranges of TB levels.